Impact of solar radiation and environmental temperature on Art Nouveau glass windows - Palomar, Teresa (2021)
Fundacao para a Ciencia e Tecnologia of Portugal (Project Ref. UID/EAT/00729/2019). Fundacion General CSIC of Spain (ComFuturo Programme). We also acknowledge support of the publication fee by the CSIC Open Access Publication Support Initiative through its Unit of Information Resources for Research (URICI).